PHP microservices : transit from monolithic architectures to highly available, scalable, and fault-tolerant microservices /: transit from monolithic architectures to highly available, scalable, and fault-tolerant microservices. (2017) - Pérez Sánchez, Carlos; Solar Vilariño, Pablo
No abstract available